Supply Chain Resilience and Carbon-Neutral Supply Chain Performance: Examining the Mediating and Moderating Role of Information Sharing Capability - Nyamvura, Elliot (University of the Witwatersrand, Johannesburg, 2024)
his study investigates the impact of supply chain resilience (SCR) on carbon-neutral supply chain performance (SCP), focusing on the mediating and moderating roles of information-sharing capabilities. Conducted within the food manufacturing and retail sectors, the research highlights how SCR, characterised by preparedness, alertness, and agility, is crucial for sustaining operations and achieving carbon neutrality amidst disruptions. The findings underscore that robust information-sharing capabilities enhance the effectiveness of SCR, enabling organisations to better manage disruptions, reduce inefficiencies, and lower carbon emissions. By fostering collaboration and communication among supply chain partners, firms can optimise logistics, engage suppliers in sustainable practices, and enhance overall environmental performance. This study provides empirical evidence supporting the integration of SCR and information-sharing capabilities as strategic tools to achieve carbon-neutral goals. The insights gained offer valuable implications for policymakers and business leaders aiming to balance economic growth with environmental sustainability. The research contributes to the existing literature by providing a comprehensive framework that underscores the importance of SCR and information sharing in achieving sustainable supply chain practices. It also suggests that adopting a holistic approach that includes these factors is critical for businesses transitioning to a low-carbon economy.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Faculty of Commerce, Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Supply chain resilience; Supply chain performance; Collaboration activities; Risk management culture; SDG-8: Decent work and economic growth